THE IMPORTANCE OF CREATIVE TASKS AND GAMES IN TEACHING ENGLISH TO PRESCHOOL CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article talks about the importance of creative tasks in teaching English to preschool children, and also suggests ways to improve children's intelligence, speed and memorization of new words through the use of various creative games for preschoolers.